Development of decorative enamels for goldware, silverware and copperware - Рижова, Ольга Петрівна; Гуржій, Ольга Борисівна (Technology audit and production reserves, 2016)
The paper analyzed the characteristics of decorative enamels for goldware, silverware and copperware. The main types of jewelry enamels and techniques for obtaining products using special application techniques were considered, as well as the requirements to them were formulated. Analysis of the current state of production of decorative enamels and their products is given. The results of the development of low-melting lead-free opacified enamel with high gloss are given. It is investigated an effect of additives TiO2, MoO3, Fe2O3 on the properties of lead-free glass and enamel coatings based on it. It is detected component (MoO3) and its rational amount (3,0 wt. %) to obtain a white enamel coating, which can be used as a basis for the light-colored enamels. Lead-free glass coatings were obtained on copper with diffuse reflection factor (DRF) to 67 %, the specular reflection factor (SRF) to 72 %. Developed green, mustard, purple, blue, brown and enamel glass coatings with high gloss have good adhesion to copper samples and may be recommended for testing under production conditions. The paper shows the possibility of enamel coatings of different colors and shades for art and jewelry application on the glass base of the same chemical composition of different chromophores.